Tính: \(3x^{2013}+5x^{2011}+2006\) . với \(x=\sqrt{6+2\sqrt{2}.\sqrt{3-\sqrt{\sqrt{2}+2\sqrt{3}+\sqrt{18+8\sqrt{2}}}}}-\sqrt{3}\)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) \(P=\frac{3x-9}{x^2-5x+6}-\frac{x+3}{x-2}-\frac{2x+1}{3-x}\)
\(P=\frac{3\left(x-9\right)}{\left(x-3\right)\left(x-2\right)}-\frac{x+3}{x-2}-\frac{2x+1}{3-x}\)
\(P=\frac{3}{x-2}-\frac{x+3}{x-2}-\frac{2x+1}{3-x}\)
\(P=\frac{3\left(3-x\right)-\left(x+3\right)\left(3-x\right)-\left(2x+1\right)\left(x-2\right)}{\left(x-2\right)\left(3-x\right)}\)
\(P=\frac{9-3x-9+x^2-2x^2+4x-x+2}{\left(x-2\right)\left(3-x\right)}\)
\(P=\frac{2-x^2}{\left(x-2\right)\left(3-x\right)}\) (*)
b) Thay \(x=-\frac{1}{2}\) vào (*) ta có:
\(P=\frac{2-\left(-\frac{1}{2}\right)^2}{\left[\left(-\frac{1}{2}\right)-2\right]\left[3-\left(-\frac{1}{2}\right)\right]}=\frac{2-\frac{1}{4}}{-\frac{5}{2}.\frac{7}{2}}=-\frac{\frac{7}{4}}{\frac{5}{2}.\frac{7}{2}}=-\frac{7}{35}=-\frac{1}{5}\)
c) \(\frac{2-x^2}{\left(x-2\right)\left(3-x\right)}< 0\)
\(\Leftrightarrow2-x^2< 0\)
\(\Leftrightarrow-x^2< -2\)
\(\Leftrightarrow x^2>2\)
\(\Leftrightarrow\hept{\begin{cases}x< -\sqrt{2}\\-\sqrt{2}< x< \sqrt{2}\\x>2\end{cases}}\)
Vậy: ...
\(\frac{x}{\sqrt{x}+\sqrt{y}}-\frac{y}{\sqrt{x}+\sqrt{y}}=\frac{\left(\sqrt{x}+\sqrt{y}\right)\left(\sqrt{x}-\sqrt{y}\right)}{\sqrt{x}+\sqrt{y}}=\sqrt{x}-\sqrt{y}\)
\(tt:\frac{y-z}{\sqrt{y}+\sqrt{z}}=\sqrt{y}-\sqrt{z};.....\)
\(\Rightarrow\frac{x}{\sqrt{x}+\sqrt{y}}-\frac{y}{\sqrt{y}+\sqrt{x}}+.....-\frac{x}{\sqrt{x}+\sqrt{z}}=0\Rightarrow dpcm\)